Regulation of commercial banks and non-bank financial institutions (NFIs) in Trinidad and Tobago : the Financial Instutitions Act, 1993. - VICTOR, Roland (1993)
Explains some of the new and expanded powers provided to the Central Bank to regulate and supervise banks and financial institutions, and attempts to explain the rationale for the inclusion of these powers in the Financial Institutions Act. Sees the new legislation as an important step in the restructuring of the financial industry which forms part of a wider process of financial and economic reform.